Using an Outdoor Learning Space to Teach Sustainability and Material Processes in HE Product Design. (October 2016) - Firth, Richard; Stoltenberg, Einar; Jennings, Trent
Abstract: This 'case study' of two jewellery workshops, used outdoor learning spaces to explore both its impact on learning outcomes and to introduce some key principles of sustainable working methodologies and practices. Using the beach as the classroom, academics and students from a Norwegian and Scottish (HE) product design exchange programme collaborated on this international research project. Participants made models from disposable packaging materials, which were cast in pewter, directly into the sand, using found timber to create a heat source for melting the metal. Practical 'learning by making skills' created a hands on learning experience that also aimed to contribute to the debate around the concern of the loss of workshop facilities in HE education, and as a consequence a demise in teaching traditional object‐making skills and material experimentation.